Legal environment and operation of general aviation aerodromes – the overview - Henryk JAFERNIK; Radosław FELLNER (Scientific Journal of Silesian University of Technology. Series Transport)
The functioning of general aviation aerodromes in Poland are regulated by more than 20 national and international legal acts. Knowledge about air law and its application ensures safe operations and flights at aerodromes and airfields. This paper summarizes source of law for general aviation and associated with its development strategies and reports. In the development of general aviation important role play small aerodromes, which are a “meeting point” for air transport sector and local economy, increase investments and tourism attractiveness of the region as well as are "meaningful way for the development of the region". Despite this, there is no legal act comprehensively regulating the issue of financial support for investment at important local aerodromes.